Climate effects and bottom‐up controls on growth and size‐at‐age of Pacific halibut (Hippoglossus stenolepis) in Alaska (USA). (21st December 2018) - Holsman, Kirstin K.; Aydin, Kerim; Sullivan, Jane; Hurst, Tom; Kruse, Gordon H.
Abstract: Pacific halibut ( Hippoglossus stenolepis ) are an ecologically, commercially, and culturally important Alaskan groundfish species. Commercial harvest of halibut dates back to the late 19th century and has been managed by the International Pacific Halibut Commission (IPHC) since 1921. IPHC surveys have revealed declining trends in survey biomass in multiple regions and region‐specific declines in mean size‐at‐age (size‐at‐age) over the past two decades (>50% in some areas). Changes in size‐at‐age can arise from a variety of physical, ecological, sampling, and fishery effects, including size‐dependent fishery or predation mortality, alteration in growth from variability in prey quality or quantity, and changes in temperature‐dependent metabolic demands. Here, we develop and apply a bioenergetics model for halibut using survey‐based diet and temperature data for Alaska to evaluate potential environmental drivers of size‐at‐age. In general, juvenile (<40 cm fork length) foraging rates were highest in the Gulf of Alaska concomitant with higher potential growth and elevated basal metabolic demands during warm summer conditions. In contrast, adult (40–120 cm FL) potential growth was highest in the Eastern Bering Sea, potentially reflecting lower metabolic costs and higher rates of prey consumption in that region. We additionally find evidence for interannual variation in potential growth, with a higher frequency of reduced growth potential in the last decade, particularly in the Eastern Bering Sea in 2015 and 2016 for both juvenile and adult halibut. These results suggest the potential for patterns in size‐at‐age to arise from trophic and environmental constraints that collectively limit growth in some regions and years.